Material flows and stocks of a service company from Debrecen - Harazin, Piroska; Dezső, Gréta Judit; Karcagi-Kováts, Andrea (International Journal of Engineering and Management Sciences, 2019)
Over the past 25 years, many renowned scientists from a number of research institutes have developed a new research method, a new family of methodologies which is the MFA (Material Flow Analysis). The importance of MFA is given by the extent of excited material flows created by mankind. The basis of MFA's growing success is a radically new, interdisciplinary vision that requires collaboration between the natural and social sciences (ecology, thermodynamics, and economics), not only as an effective tool for examining material efficiency of production and environmental pressures, as well as the security of supply of the strategic material requirements of the system under investigation. In our article, we conduct an enterprise level analysis of the input and output side material flows and materials of a service company in Debrecen for 2018 using the MFA method. MFA indicators capture environmental pressures in a natural dimension, that is, in terms of mass, energy, or land, respectively, in terms of kilograms or tons, of the company's raw materials and their changes, or material inputs.